Reversing deleterious protein aggregation with re-engineered protein disaggregases - Jackrel, Meredith E (Landes Bioscience, 2014)
Aberrant protein folding is severely problematic and manifests in numerous disorders, including amyotrophic lateral sclerosis (ALS), Parkinson disease (PD), Huntington disease (HD), and Alzheimer disease (AD). Patients with each of these disorders are characterized by the accumulation of mislocalized protein deposits. Treatments for these disorders remain palliative, and no available therapeutics eliminate the underlying toxic conformers. An intriguing approach to reverse deleterious protein misfolding is to upregulate chaperones to restore proteostasis. We recently reported our work to re-engineer a prion disaggregase from yeast, Hsp104, to reverse protein misfolding implicated in human disease. These potentiated Hsp104 variants suppress TDP-43, FUS, and α-synuclein toxicity in yeast, eliminate aggregates, reverse cellular mislocalization, and suppress dopaminergic neurodegeneration in an animal model of PD. Here, we discuss this work and its context, as well as approaches for further developing potentiated Hsp104 variants for application in reversing protein-misfolding disorders.